(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
This article examines the international experience of using information technologies in physical education, sports, and fitness. The study analyzes various software products and mobile applications widely used in these fields across different countries, providing a comprehensive overview of current trends and best practices. The research highlights several key categories of technology applications, including information-diagnostic systems, functional fitness assessment tools, biomechanical analysis software, and health and fitness apps. The paper discusses prominent examples such as FitnessGram, Canadian Assessment of Physical Literacy (CAPL), ALPHA-FIT test, and the Youth Physical Development Model, exploring their impact on physical education and fitness assessment. In the realm of biomechanical analysis, the article explores professional systems like SIMI Motion and Qualisys Track Manager, as well as more accessible options such as Dartfish and Kinovea, evaluating their effectiveness in improving movement techniques and preventing injuries. The study also examines popular fitness applications like MyFitnessPal, Strava, and Nike Training Club, discussing their features and impact on physical activity and health management. The research emphasizes the growing importance of these technologies in enhancing the effectiveness of physical education, optimizing sports performance, and promoting healthy lifestyles. The article concludes by highlighting the potential of these technologies to revolutionize approaches to physical education, sports training, and personal fitness. It also identifies areas for future research, including the adaptation of foreign technologies to local contexts, the integration of artificial intelligence and augmented reality in physical education, and the need for experimental studies to assess the impact of these technologies on students’ physical fitness and motivation.